2022
DOI: 10.3390/genes13060994
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Senescence in Normal Mammary Gland and Breast Cancer. Implications for Cancer Therapy

Abstract: Cellular senescence (CS) is a major homeostatic biological process, which plays a key role in normal tissue development and provides protection from stressful cell insults. The role of CS in mammary-gland development and breast cancer is not well understood. While there is a lack of experimental data on the role of CS in the development of the pre-pubertal mammary gland, there is evidence for a biphasic senescence response in adult normal-mammary-epithelial cells, where the bypass of the first senescence barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Cellular senescence plays an important role in benign and malignant tissue, especially as a treatment resistance mechanism, but the specific role in TNBC carcinogenesis remains unclear. It is known that MCF10A cell lines can escape senescence upon HRAS overexpression, suggesting that senescence might play a relevant role in tissue transformation ( 36 ). On the other hand, a study evaluating the stroma of chemotherapy-naïve older patients with TNBC showed, among other senescent-related genes, the presence of SASP.…”
Section: Triple Negative and Senescencementioning
confidence: 99%
“…Cellular senescence plays an important role in benign and malignant tissue, especially as a treatment resistance mechanism, but the specific role in TNBC carcinogenesis remains unclear. It is known that MCF10A cell lines can escape senescence upon HRAS overexpression, suggesting that senescence might play a relevant role in tissue transformation ( 36 ). On the other hand, a study evaluating the stroma of chemotherapy-naïve older patients with TNBC showed, among other senescent-related genes, the presence of SASP.…”
Section: Triple Negative and Senescencementioning
confidence: 99%
“…The escape‐from‐senescence phenomenon could also be a mechanism contributing to this outcome (see the next section). Ever since GL13 discovery, the spectrum of pathological entities has been expanded to include benign, preneoplastic, and neoplastic lesions, while senescent cells have also been recognised in various experimental and ageing contexts (Table 2) [37,106,107,110–137]. In particular, in clinical settings, skin pathologies (nevi, seborrheic, and actinic keratoses), lung, pancreatic, urothelial and laryngeal precancerous lesions, various types of carcinomas following treatment, sarcomas, haematological malignancies (Langerhans histiocytosis), and a variety of tissues from aged organs were included (Table 2).…”
Section: Detecting Senescence Escape: a Challenging Taskmentioning
confidence: 99%
“…The SASP was therefore suggested to regulate OIS in PA [ 225 ] and held responsible for the slow growth pattern, the lack of progression to higher-grade astrocytomas and the high OS of affected patients [ 224 ]. In addition, no oncogene-induced or therapy-induced senescent cells were identified in chemotherapy-naïve and neoadjuvant chemotherapy treated breast cancer samples, suggesting tumoral senescent cells either were already cleared by the immune system or bypassed senescence [ 151 ].…”
Section: Main Textmentioning
confidence: 99%